2000
DOI: 10.1034/j.1398-9995.2000.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective upregulation of a functional β7 integrin on differentiating eosinophils

Abstract: Our data show that protein synthesis-dependent upregulation of the functional beta7 integrin occurs under conditions when beta4 and beta1 integrins are fully expressed, indicating a sequential appearance of specific adhesion molecules on differentiating eosinophil progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Sequential up‐regulation of the β integrins on progenitors has been the proposed mechanism to support the efflux of these cells from the bone marrow. Experiments that induced HL60 cells towards eosinophil differentiation showed a significant up‐regulation of functional β7 integrin expression coincident with down‐regulation of β1 integrin expression [65]. Subsequent studies confirmed and extended these findings, demonstrating up‐regulation of β7 integrin and down‐regulation of β1 and α5 integrins on cord blood progenitors during eosinophil differentiation [66], and thus suggesting the requirement for specific adhesion at distinct stages of cell maturation.…”
Section: Bone Marrowmentioning
confidence: 92%
“…Sequential up‐regulation of the β integrins on progenitors has been the proposed mechanism to support the efflux of these cells from the bone marrow. Experiments that induced HL60 cells towards eosinophil differentiation showed a significant up‐regulation of functional β7 integrin expression coincident with down‐regulation of β1 integrin expression [65]. Subsequent studies confirmed and extended these findings, demonstrating up‐regulation of β7 integrin and down‐regulation of β1 and α5 integrins on cord blood progenitors during eosinophil differentiation [66], and thus suggesting the requirement for specific adhesion at distinct stages of cell maturation.…”
Section: Bone Marrowmentioning
confidence: 92%
“…Even though their role in eosinophil development remains unexplored, a4 integrin heterodimers are differentially regulated during terminal differentiation [16,17]. Here, we show that, in developing eosinophils, dexamethasone increases a4 integrin expression, and that treatments targeting a4 integrins induce dissociation and cytological maturation, supporting a regulatory role for a4 integrins during terminal differentiation.…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we focused on a4 integrins, the bestcharacterized eosinophil integrins [11], because they were previously shown to influence the development of several haemopoietic lineages other than eosinophils, as follows: (a) a4b1 integrin mediates haemopoietic progenitor adhesion to VCAM-1-and fibronectin-expressing BM stroma [12]; (b) haemopoietic progenitors constitutively express a4b1 with high affinity [13]; (c) anti-a4b1 integrin antibodies block development of lymphoid and myeloid cells [12,14]; and (d) haemopoietic progenitor retention inside BM is a4 integrindependent [15]. Even though their role in eosinophil development remains unexplored, a4 integrin heterodimers are differentially regulated during terminal differentiation [16,17]. Here, we show that, in developing eosinophils, dexamethasone increases a4 integrin expression, and that treatments targeting a4 integrins induce dissociation and cytological maturation, supporting a regulatory role for a4 integrins during terminal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…An important mechanism for the selective recruitment of eosinophils to sites of allergic inflammation is by regulation of adhesion pathways such as β 2 integrin/ICAM-1, VLA-4/VCAM-1 and integrin β 7 [25,26,27]. DL has been shown to downregulate the adhesion molecule ICAM-1 [28, 29], which binds to its natural ligand LFA-1 present on eosinophils [30] and CD34+ progenitors [25, 26].…”
Section: Discussionmentioning
confidence: 99%